2018
DOI: 10.1332/174426417x14945838375115
|View full text |Cite
|
Sign up to set email alerts
|

A recipe for impact? Exploring knowledge requirements in the UK Parliament and beyond

Abstract: In the context of ongoing debates around academic engagements with policymakers, this article discusses how academics can successfully engage with the often overlooked institution of Parliament. We argue that the UK Parliament is not a homogeneous organisation but has differing knowledge requirements for different parliamentary sites. While there are common barriers that need to be overcome by researchers, there is no universal recipe that will ensure successful research impact. We argue that there are differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
(24 reference statements)
0
19
0
5
Order By: Relevance
“…However, a recent and substantial study examining the role of research in the UK Parliament revealed that although research in its broadest sense is useful for parliamentary work, academic research is ‘ not cutting through ’ [9]. The study revealed that challenges to the use of academic research included lack of accessibility and poor communication [9], which mirrored findings from an earlier study of eight UK parliamentary staff [10]. Yet there remains a gap in knowledge regarding the challenges and motivations for research professionals to engage with evidence-informed policy-making processes.…”
Section: Introductionmentioning
confidence: 84%
“…However, a recent and substantial study examining the role of research in the UK Parliament revealed that although research in its broadest sense is useful for parliamentary work, academic research is ‘ not cutting through ’ [9]. The study revealed that challenges to the use of academic research included lack of accessibility and poor communication [9], which mirrored findings from an earlier study of eight UK parliamentary staff [10]. Yet there remains a gap in knowledge regarding the challenges and motivations for research professionals to engage with evidence-informed policy-making processes.…”
Section: Introductionmentioning
confidence: 84%
“…Should academics help ‘co-produce’ knowledge and policy with others? Co-production is often hailed as the most useful way to promote research evidence in policy (Geddes et al, 2018) but, to do so in a meaningful way, researchers must cede control over the research agenda (Flinders et al, 2016; Matthews et al, 2017). There are reputational risks: it can prompt accusations of bias, partisanship, or partiality for one political view over another.…”
Section: Seeking Impact: When Safe Advice Meets Professional Dilemmasmentioning
confidence: 99%
“…The definitive publisher-authenticated version (doi:10.1057/s41293-018-0083-y) is available online at: https: //link.springer.com/article/10.1057/s41293-018-0083-y accordingly become an essential yardstick for justifying the allocation of public funds to pay for it, reflecting a shift 'from a state patronage to investment model' of research funding (Hammersley, 2014, p. 345). In the social sciences impact has typically been understood in terms affecting public policy, particularly in the context of the desire for more 'evidence-based' policy (Geddes et al, 2017).…”
Section: The Impact Agenda In Uk Higher Educationmentioning
confidence: 99%